From Smart Dynamic Casting to a growing family of Digital Casting Systems. (August 2020) - Lloret-Fritschi, Ena; Wangler, Timothy; Gebhard, Lukas; Mata-Falcón, Jaime; Mantellato, Sara; Scotto, Fabio; Burger, Joris; Szabo, Anna; Ruffray, Nicholas; Reiter, Lex; Boscaro, Federica; Kaufmann, Walter; et al.
Abstract: Over the past decade innovative techniques for shaping concrete have emerged, all aiming to use less material and reduce the need for traditional formwork. One very promising method is to shape concrete dynamically: referred to as Smart Dynamic Casting (SDC), this process was pioneered in 2012 as the first robotically-driven system for slipforming bespoke concrete structures. The process has successfully been adapted to produce structures using ultra-thin formworks that are cast using our digital set-on-demand procedure. More generally we frame this approach as Digital Casting Systems (DCS), which allows the user precisely to determine the hydration rate of the material, thus eliminating formwork pressure. This paper highlights the major findings from SDC that led us to continue developing DCS. It lays out the material concepts fundamental the family of DCS, which, by eliminating the need for bulky formworks, has a large potential impact on future construction methods.